Frequency of refluxive tributaries of the junction region in the groin in patients with recurrent varicose veins of the thigh - Reich-Schupke, S.; Mendoza, E.; Dörler, M.; Stücker, M. (Phlebologie, 2016)
Background A long stump and neovascularisation are commonly discussed reasons for recurrence of varicosis in the groin after “disconnection” of the saphenofemoral junction (SFJ) and stripping of the great saphenous vein (GSV). A third possible reason for recurrence with non femoral reflux emerging from tributaries of the junction region, is often underrated. The aim of the study was to report on the source of reflux for recurrent varicose veins of the thigh in patients who already had a history of disconnection of the SFJ and stripping of the GSV.Methods In this two-centre study, consecutive patients with a history of disconnection of the SFJ, stripping of the GSV and visible or palpable varicose veins of the thigh region were included. Their data and venous diagnostics (DPPG, duplex scan) were recorded and evaluated by a standardised protocol.Results 101 legs were included. In 58.4 % there was a long stump of the GSV as a source for variose veins of the thigh. In the other legs (42,6 %) the source for the reflux was not a long stump with contact to the femoral vein but residual tributaries of the SFJ, e.g. the superficial epigastric vein or the superficial circumflex iliac vein.Conclusions Residual refluxive tributaries of the SFJ seem to be an important source for recurrent varicose veins of the thigh. Further prospective studies should focus on suitable therapeutic options.
Keywords: Recurrence; saphenofemoral junction; varicose veins; duplex